Is supernatural belief unreliably formed? - Eyghen, Hans van ca. 21. Jh. (International journal for philosophy of religion, 2019)
I criticize 5 arguments for the conclusion that religious belief is unreliably formed and hence epistemically tainted. The arguments draw on scientific evidence from Cognitive Science of Religion. They differ considerably as to why the evidence points to unreliability. Two arguments conclude to unreliability because religious belief is shaped by evolutionary pressures; another argument states that the mechanism responsible for religious belief produces many false god-beliefs; a similar argument claims that the mechanism produces incompatible god-beliefs; and a final argument states that the mechanism is offtrack. I argue that the arguments fail to make the case for unreliability or that the unreliability can be overcome.